Meteorological sub-divisions of India and their geopolitical evolution from 1875 to 2020 - R. R., KELKAR; O. P., SREEJITH (MAUSAM, 2020)
The great diversity of the weather and climate of India prompted the India Meteorological Department (IMD) soon after its establishment in 1875 to delineate its own meteorological provinces that were different from political ones. These provinces, now known as meteorological sub-divisions, changed in number, nomenclature and spatial extent, over the years from 1875 to 2020. The present paper traces the heritage of IMD’s 36 meteorological sub-divisions as of 2020 to the past, in terms of history, geography and political changes.